Ecological estimation of winter peas in the conditions of the southern part of the Rostov region - A. R. Ashiev; M. V. Skulova; K. N. Khabibullin (Зерновое хозяйство России)
The current paper has presented the study results on the ecological estimation of seed peas of different types of development. The purpose of our study was to assess the quantitative and qualitative indicators of seed peas varieties of different types of development in the southern part of the Rostov region. The trials were carried out on the experimental plots of the FSBSI “Agricultural Research Center “Donskoy” at the laboratory for legumes breeding and seed production. Autumn sowing was carried out in the second decade of October. Spring sowing was conducted in the third decade of March. The objects of the study were the variety ‘Legion’ sown in autumn and spring in comparison with the variety ‘Aksaysky Usatiy 5’, which was used as a standard variety in the trials. The statistical data were processed according to B. A. Dospekhov’s methodology (2012) using Excel with the STATISTICA 10 application. The variety ‘Legion’ sown in autumn ripened earlier in comparison with the standard variety ‘Aksaysky Usatiy 5’. Early ripening of winter peas than spring peas made it possible to evenly distribute the load on the harvesting equipment, since ripening of spring peas often coincided with ripening of winter grain crops, such as winter barley and winter wheat. The variety ‘Legion’ sown in winter exceeded the standard variety ‘Aksaysky Usatiy 5’ in such indicators as “plant height”, “number of beans”, “number of seeds”, “seed weight per plant” and “protein percentage”. The study results have shown that the conditions of the southern part of the Rostov region were favorable for the cultivation of winter peas. The winter peas ripened a decade earlier than spring peas, and seed productivity was 1.7–1.8 times larger.